Development of a core outcome set for trials for management of oral submucous fibrosis (OSFCOS): A consensus study protocol - Shailesh M. Gondivkar; Monal Yuwanati; Sachin C. Sarode; Amol R. Gadbail; Vidya Lohe (PLoS ONE, 2025)
Background The effectiveness of oral submucous fibrosis (OSF) treatment is currently assessed with a broad range of clinical outcome measures. This heterogeneity complicates study comparison, synthesis of results, and evidence-based clinical practice guideline development. A core outcome set (COS) is a set of agreed, standardized outcomes that will be measured and reported across all clinical trials for a particular condition. Objective Our aim is to create a COS (OSFCOS) for efficacy trials that look at the management OSF. Methods An initial list of the potentially relevant outcomes will be drawn by a systematic review of randomized controlled trials focused on OSF treatment. An e-Delphi process will be done to obtain agreement among important stakeholders. The stakeholders will consist of OSF patients, members of the Indian Academy of Oral Medicine & Radiology, the representatives from the Indian Dental Association, clinical researchers, and other oral health specialists. Participants will be asked to rate the importance of each outcome on a structured online questionnaire. Participants will also be allowed to propose new outcomes in Round 1. Feedback and the aggregated scores will be given in later rounds to guide re-rating. If after the second round, there is still no consensus, a third round will be taken.Final consensus on outcome inclusion will be determined based on predefined criteria. Conclusion This protocol outlines a structured, inclusive approach to developing a core outcome set for OSF. The finalized OSFCOS will be made publicly available to guide outcome selection in clinical trials, improve the quality of systematic reviews, and support evidence-based clinical recommendations for the treatment of OSF.